2016
DOI: 10.1111/ejn.13477
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala mu‐opioid receptors mediate the motivating influence of cue‐triggered reward expectations

Abstract: Environmental reward-predictive stimuli can retrieve from memory a specific reward expectation that allows them to motivate action and guide choice. This process requires the basolateral amygdala (BLA), but little is known about the signaling systems necessary within this structure. Here we examined the role of the neuromodulatory opioid receptor system in the BLA in such cue-directed action using the outcome-specific Pavlovian-to-instrumental transfer (PIT) test in rats. Inactivation of BLA mu-, but not delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…We also found the BLA to be necessary, specifically at the time of stimulus-reward pairing, to encode the detailed stimulus-outcome memories. This is consistent with evidence that either pre-or post-training BLA lesion or pre-test inactivation disrupts appetitive conditional behaviors that rely on a sensory-specific, stimulusoutcome memory in rodents (Blundell et al, 2001;Corbit & Balleine, 2005;Derman et al, 2020;Hatfield et al, 1996;Lichtenberg et al, 2017;Lichtenberg & Wassum, 2016;Malvaez et al, 2015;Morse et al, 2020;Ostlund & Balleine, 2008) and in primates (Murray & Izquierdo, 2007;Málková et al, 1997). Leveraging the temporal resolution of optogenetics, we demonstrated that the BLA mediates the encoding of such memories.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found the BLA to be necessary, specifically at the time of stimulus-reward pairing, to encode the detailed stimulus-outcome memories. This is consistent with evidence that either pre-or post-training BLA lesion or pre-test inactivation disrupts appetitive conditional behaviors that rely on a sensory-specific, stimulusoutcome memory in rodents (Blundell et al, 2001;Corbit & Balleine, 2005;Derman et al, 2020;Hatfield et al, 1996;Lichtenberg et al, 2017;Lichtenberg & Wassum, 2016;Malvaez et al, 2015;Morse et al, 2020;Ostlund & Balleine, 2008) and in primates (Murray & Izquierdo, 2007;Málková et al, 1997). Leveraging the temporal resolution of optogenetics, we demonstrated that the BLA mediates the encoding of such memories.…”
Section: Discussionsupporting
confidence: 91%
“…A 3-watt, 24-volt house light mounted on the top of the back wall opposite the food-delivery port provided illumination and a fan mounted to the outer chamber provided ventilation and external noise reduction. Behavioral procedures were similar to that we have described previously (Lichtenberg et al, 2017;Lichtenberg & Wassum, 2016;Malvaez et al, 2015) Magazine conditioning. Rats first received one day of training to learn where to receive the sucrose and food pellet rewards.…”
Section: Behavioral Proceduresmentioning
confidence: 99%
“…Overall, cue-controlled cocaine and heroin seeking both involve dopamine, GABA(B) (Di Ciano & Everitt, 2003), and l-opioid receptor-dependent mechanisms (Giuliano et al, 2013). The rather counter-intuitive reliance of cue-controlled drug seeking on opioidergic mechanisms may be related to their involvement in the basolateral amygdala in mediating the motivational control of CSs over instrumental performance (Lichtenberg & Wassum, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An answer to this puzzle comes by noting that MOR promotes innate responses to cues predicting reward. For example, BLA MORs facilitate vigorous approach to predictive food cues [Lichtenberg and Wassum, 2017]. Cues are learned by conditioning, so are part of the innate+ system, which extends the innate system.…”
Section: Consume: Beta-endorphin (Bend)mentioning
confidence: 99%